2019
DOI: 10.24016/2019.v5n1.135
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Burnout en Cuidadores de Pacientes con Discapacidad Infantil

Abstract: The aim of this study was to value the prevalence of burnout syndrome in caregivers of pa ents with disabili es from Arequipa City. The sample was conformed by 45 caregivers (91.42% female and 8.8% male) with and average age of 30.26 years old. We applied the Burnout Maslach Inventory, which has 22 items and three dimensions: exhaus on, cynicism and inefficacy. Its reliability is adequate for health personnel like this case (α= 0.721). The caregivers of pa ents with disability are women and rela ves of the peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2020
2020
2029
2029

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
1
1
1
Order By: Relevance
“…As the authors set out, it can be confirmed that the social system of the organizations is a highly relevant context for a person’s workplace health. However, the results diverge from those set out by Arias et al [ 58 ] and González and Veliz [ 59 ], since they stressed that, of all the professional groups evaluated, that of carers of persons with a disability was the group that showed the greatest psychosocial risk due to the high percentage of subjects suffering from burnout syndrome.…”
Section: Discussioncontrasting
confidence: 68%
“…As the authors set out, it can be confirmed that the social system of the organizations is a highly relevant context for a person’s workplace health. However, the results diverge from those set out by Arias et al [ 58 ] and González and Veliz [ 59 ], since they stressed that, of all the professional groups evaluated, that of carers of persons with a disability was the group that showed the greatest psychosocial risk due to the high percentage of subjects suffering from burnout syndrome.…”
Section: Discussioncontrasting
confidence: 68%
“…Undoubtedly, this situation can translate into stress conditions in both groups, in addition to those they may be experiencing arising from their responsibilities as teachers and students. It has been documented that caregivers of children, older adults, people with disabilities, and students and education professionals are among the groups most likely to develop burnout syndrome (Arias et al, 2019). In this case, coupling both activities due to confinement, the risk of emotional wear may increase.…”
Section: Discussionmentioning
confidence: 99%
“…Son frecuentes: el estrés, las preocupaciones por el futuro de su familiar, la incapacidad para focalizar su atención en otros ámbitos que no sea el cuidado, los sentimientos de responsabilidad y obligación y la presión personal, lo que genera un gran agotamiento mental. Así, un gran porcentaje de personas cuidadoras muestra síntomas ansiosos y depresivos (Casaña-Granell et al, 2018;Casademont, 2018;Fernández, 2018;Arias-Gallegos, Cahuana-Cuentas, Ceballos-Canaza, y Caycho-Rodríguez, 2019).…”
Section: Introductionunclassified